Effect of Convector Freezing on Sperm Survival and Fertilizing Ability After Thawing - Pavlenko, B. M. (Problems of Cryobiology and Cryomedicine, 2007)
The research results on the development, studying an practical use of portable cryoconvector for freezing of encapsulated sperm doses have been proposed. A high efficiency of this designing under production conditions when creating frozen bovine sperm in encased granules was shown.